An observational study identifying obese subgroups among older adults at increased risk of mobility disability: do perceptions of the neighborhood environment matter?. Issue 1 (December 2015) - King, Abby; Salvo, Deborah; Banda, Jorge; Ahn, David; Gill, Thomas; Miller, Michael; Newman, Anne; Fielding, Roger; Siordia, Carlos; Moore, Spencer; Folta, Sara; Spring, Bonnie; et al.
Abstract Background Obesity is an increasingly prevalent condition among older adults, yet relatively little is known about how built environment variables may be associated with obesity in older age groups. This is particularly the case for more vulnerable older adults already showing functional limitations associated with subsequent disability. Methods The Lifestyle Interventions and Independence for Elders (LIFE) trial dataset (n  = 1600) was used to explore the associations between perceived built environment variables and baseline obesity levels. Age-stratified recursive partitioning methods were applied to identify distinct subgroups with varying obesity prevalence. Results Among participants aged 70–78 years, four distinct subgroups, defined by combinations of perceived environment and race-ethnicity variables, were identified. The subgroups with the lowest obesity prevalence (45.5–59.4 %) consisted of participants who reported living in neighborhoods with higher residential density. Among participants aged 79–89 years, the subgroup (of three distinct subgroups identified) with the lowest obesity prevalence (19.4 %) consisted of non-African American/Black participants who reported living in neighborhoods with friends or acquaintances similar in demographic characteristics to themselves. Overall support for the partitioned subgroupings was obtained using mixed model regression analysis. Conclusions The results suggest that, in combination with race/ethnicity, features of the perceived neighborhood built and social environments differentiated distinct groups of vulnerable older adults from different age strata that differed in obesity prevalence. Pending further verification, the results may help to inform subsequent targeting of such subgroups for further investigation. Trial registration Clinicaltrials.gov Identifier = NCT01072500